Two new species of Stenostygnus from South America (Opiliones: Biantidae: Stenostygninae) - Mamani, Claudia Vanesa; Porto, Willians; Iglesias, Patricia P.; Pérez-González, Abel (Zootaxa, 2021)
Stenostygnus martensi spec. nov. and Stenostygnus huberi spec. nov. are described from montane localities of the States of Mérida and Lara in Venezuela, and the diagnosis of the previously monotypic genus Stenostygnus Simon, 1879, is emended. The presence of these two new species as local endemics in Andean localities of Venezuela represents a huge range extension for the genus Stenostygnus, and the new localities are also ecologically different from previously known localities in the Amazon Basin. This could indicate the presence of a rich and uncharted diversity of stenostygnines in the Andean regions, particularly in the north of South America.